TECHNICAL EFFICIENCY OF ARTISANAL FISHING ON WATERWEED INFESTED LAKES IN RIVERINE COMMUNITIES OF OGUN STATE, NIGERIA - Ologbon, O. A. C.; Ologbon, K.T.; Obasan T.A.; Dada, O.M.; Sofoluwe, N.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the technical efficiency of artisanal fishing in water weed infested lakes and riverine communities of Ogun State, Nigeria. Random sampling technique was used in selecting 120 respondents. Data were collected through the administration of questionnaire and analyzed using both descriptive and inferential statistics. The results revealed that 39.2% of the respondents were between the age bracket of 41- 50 years with a mean of 44.19 years and dominantly male (73.3%) and married (90.8%). The study further revealed that all (100%) of the fisher folks had former education ranging from primary education to tertiary education. Findings further showed that 27.5% had household size of 10-12 members with a mean of 8 persons and had between 21-30 years fishing experience. The result revealed that 62.5% of the respondents are into full-time artisanal fishing. The results of regression analysis showed that fishing time per trip (P<0.01), number of fisher folk per trip (P<0.10) and time of fishing (P<0.01) were the factors influencing the level of fish catch. Results of the stochastic frontier showed that fishing time per trip (P<0.05) and hired labour (P<0.01) were the factors influencing the technical efficiency. The mean efficiency of the fisher folks in the study area was 0.76 implying that 24% of the inefficiency of the fisher folks was caused by water weed and other unforeseen constraints. The study finally concluded that fisher folks fisher folk in the study area were technically efficient and their efficiency is influenced by fishing time and hired labour among others. The study therefore recommends that both natural and artificial coping strategies be adopted by fisher folks to improve on the technical efficiency of artisanal fish capture on water weed-infested lakes in the study area.